A convenient one-pot synthesis of ketone cyanohydrin esters in aqueous media. Issue 52 (30th December 2015) - Wet-osot, Sirawit; Pattarawarapan, Mookda; Phakhodee, Wong
Graphical abstract: Abstract: A convenient one-pot, two-step procedure for the synthesis of ketone cyanohydrin esters in aqueous media is reported using N -acylbenzotriazoles as the acylating agents. In saturated aqueous sodium bicarbonate containing a catalytic amount of tetrabutylammonium bromide, the reaction of ketones with potassium cyanide and N -acylbenzotriazoles proceeded readily at room temperature to provide the corresponding O -acyl cyanohydrin derivatives in good to excellent yields.